The role of logistics in e-commerce - George, Joseph (2008)
Click. Shopping is now as easy as the press of a button from the comfort of one's home. The Internet has revolutionized the way business is conducted. When the online shopping business started growing, many prophesied that it was the end of the road for many of the intermediaries, who were dominant in traditional supply chains, as more and more suppliers and manufacturers were likely to prefer selling direct to the customer in order to reduce delivery time, costs and compete in the online market. This meant that most of the business for logistics service providers would be mainly limited to the last mile of the online shopping order cycle. However, this has not been the case and the logistics service providers dealing with internet shopping have witnessed tremendous growth in business. The focus of this report is to review the role of logistics service providers or 3PL in online/internet shopping and to study the importance of their services in internet shopping or e-tailing. The importance aspect will be analysed through statistical analysis based on online customer feedback and by trying to forge links, if any, between customer loyalty to an online supplier and logistics related activities like order processing, warehousing and delivery. Another aim of this research is to determine the level of importance of logistics for different product types. Furthermore, qualitative analysis of data obtained from primary and secondary interviews will be used to conclude whether logistics providers have been positively or negatively affected by the advent of internet shopping.